Diabetic Ketoacidosis in Children and Adolescents; Diagnostic and Therapeutic Pitfalls - Eirini Kostopoulou; Xenophon Sinopidis; Sotirios Fouzas; Despoina Gkentzi; Theodore Dassios; Stylianos Roupakias; Gabriel Dimitriou (Diagnostics, 2023)
Diabetic ketoacidosis (DKA) represents an acute, severe complication of relative insulin deficiency and a common presentation of Type 1 Diabetes Mellitus (T1DM) primarily and, occasionally, Type 2 Diabetes Mellitus (T2DM) in children and adolescents. It is characterized by the biochemical triad of hyperglycaemia, ketonaemia and/or ketonuria, and acidaemia. Clinical symptoms include dehydration, tachypnoea, gastrointestinal symptoms, and reduced level of consciousness, precipitated by a variably long period of polyuria, polydipsia, and weight loss. The present review aims to summarize potential pitfalls in the diagnosis and management of DKA. A literature review was conducted using the Pubmed/Medline and Scopus databases including articles published from 2000 onwards. Diagnostic challenges include differentiating between T1DM and T2DM, between DKA and hyperosmolar hyperglycaemic state (HHS), and between DKA and alternative diagnoses presenting with overlapping symptoms, such as pneumonia, asthma exacerbation, urinary tract infection, gastroenteritis, acute abdomen, and central nervous system infection. The mainstays of DKA management include careful fluid resuscitation, timely intravenous insulin administration, restoration of shifting electrolyte disorders and addressing underlying precipitating factors. However, evidence suggests that optimal treatment remains a therapeutic challenge. Accurate and rapid diagnosis, prompt intervention, and meticulous monitoring are of major importance to break the vicious cycle of life-threatening events and prevent severe complications during this potentially fatal medical emergency.